Analisis Keamanan Siber Sistem Informasi Perpustakaan di Perpustakaan Universitas Jenderal Soedirman - Nurochman, Arif; Astuti, Endah Yuni; Widianingtias, Sayekti (BACA: Jurnal Dokumentasi dan Informasi, 2024)
The implementation of web technologies in libraries faces challenges from acts of sabotage and cybersecurity, despite the ease of access to information being its main feature. The purpose of this study is to describe the analysis of information system cybersecurity at the Universitas Jenderal Soedirman (Unsoed) library using the NIST cybersecurity framework for the functions of identifying, protecting, detecting, responding, and recovering. Research informants consist of librarians who interact with information systems. The research method used was qualitative with a case study approach with in-depth interviews and observations. The results describe the function of identifying security processes according to the capabilities of librarians. The protect function identifies the identity management process and system vulnerabilities in the form of bugs and forms infiltrated by hackers. The detect function identifies infiltration from abroad. The respond function is handled by the administrator by restoring the server and is incidental after an event. The restore function plans actions to establish communication with library stakeholders. Technical recovery with default security systems and carrying out evaluation of enhancements developed in the system development life cycle continuously. Cybersecurity analysis using the NIST cybersecurity framework can describe the technical and managerial level of security in the application infrastructure so as to anticipate the possibility of cyber attacks.